(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
This comprehensive article delves into the intricate composition of water and the multifaceted methods used for its purification. It highlights the often-overlooked complexity of water, containing not just H2O molecules but a myriad of dissolved minerals, organic materials, and potential pollutants. The article methodically examines analytical techniques such as spectroscopy and chromatography, and explores purification methods like reverse osmosis and ion exchange with practical examples and case studies.